Prototype of the information application provided by the patient for urgency and emergency moments - Bruna Aparecida Polido; Elias César Araújo de Carvalho (Acta Scientiarum. Health Sciences, 2024)
During an emergency and urgent care, there is great difficulty on the part of health professionals who attend the event to trust the data provided, especially when these are provided by patients who may not be mentally well, in shock, without communication or even the absence of the informant when the patient is unconscious. Therefore, this study aims to develop a prototype to validate the fundamental requirements for creating an application that contains basic patient data that are essential for their care. In addition to personal data, the patient will be able to inform data about allergies, pre-existing diseases and continuous medication use. In this way, this application will help the healthcare professional to obtain this information in a clear, easy and organized way. As a methodology, the scenario was studied, during this phase, meetings were held with professionals from the urgency and emergency service and, with that, the main requirements for the development of the prototype were elaborated. Then, the development of the prototype began.(patient and/or his/her guardian) (attendant health professional). The prototype was developed using the Lean methodology, which deals with continuous learning and a focus on team communication, and Scrum, a methodology focused on continuous development and approval and the use of features and usability. With the prototype ready, an explanatory video was made about the functioning of the prototype. Then, an interview was carried out with some health professionals, via Face book high lighted by this study and the use of the about app. The survey results showed that 96.2% of respondents said they would use the application, 93.2% would feel safer during an emergency care and 79.2% would like to be informed if the application is completed. The prototype was elaborated, evaluated and the results showed that the product is viable.